Hybrid on-demand greedy routing protocol with backtracking for mobile ad-hoc networks. Issue 1 (2nd January 2020) - Mahmood, Baban A.; Manivanann, Dakshnamoorthy
Abstract : Purpose: The purpose of this paper is to design an efficient on-demand routing protocol for mobile ad hoc networks (MANETs) which combines greedy forwarding and backtracking. Design/methodology/approach: It uses a hybrid approach. It uses greedy approach to determine a route from source to the destination. If the greedy approach fails, then it uses a backtracking approach. Combining greedy and backtracking approaches results in a more efficient protocol. Findings: A new routing algorithm for MANETs which performs better than some of the existing algorithms. Research limitations/implications: A major limitation of this work is that the authors did not implement the protocol on a test bed and evaluated the performance. They neither had the infrastructure nor the resources to actually implement the protocol. Instead, like most of the researchers, they evaluated the performance of their protocol based on extensive simulation. The mobility model, the area of deployment and the density of nodes chosen to simulate the protocol are consistent with what many of the other researchers have done. Intuitively, the authors' protocol, as the performance evaluation indicates, is likely to perform well in small networks. Practical implications: The authors did not implement the protocol on a test bed to evaluate the performance of the protocol. The authors used simulation to study the performance of their protocol. Their simulation model is similar to many of the research works published in the literature. Originality/value: To the authors' knowledge, no other paper has combined the greedy and backtracking approach to design a routing protocols for MANETs.